2019
DOI: 10.31609/jpmrs.2019-66862
|View full text |Cite
|
Sign up to set email alerts
|

Does Kinesiophobia Associated with Poststroke Neuropathic Pain and Stroke Severity?

Abstract: inesiophobia is defined as fear of acting due to belief of predisposition to injury. It causes physical activity limitation. In the continuation of chronic pain, pain-related fear significantly contributes the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…This area of disease has so far been poorly researched, and reports are scarce. The presented results, as well as previous studies, indicate that the scale of this problem is large [ 22 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 82%
“…This area of disease has so far been poorly researched, and reports are scarce. The presented results, as well as previous studies, indicate that the scale of this problem is large [ 22 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 82%
“…As in our study, other authors have also shown a high prevalence of kinesiophobia in elderly stroke patients. 11 , 12 According to Wasiuk-Zawada et al, the incidence of kinesiophobia varied depending on the degree of motor disability according to Rankin, including 83.3% of patients with mild disabilities and 73.1% of patients with moderate disabilities. 12 In the above studies 11 , 12 and in our study, kinesiophobia was defined on the basis of the TSK criterion, which allowed for a comparative analysis of the frequency of this phenomenon, which turned out to be high in the majority of stroke patients in studies from various centers.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, an increased incidence of kinesiophobia in stroke patients was positively correlated with advanced age, disease duration and stroke severity. 11 Moreover, it was observed that post-stroke kinesiophobia was related to a fear of falling. 13 Our observations show that the intensity of kinesiophobia in patients with stroke showed correlation with a higher level of anxiety assessed with the use of HADS, higher TFI value for the frailty syndrome, and a low level of acceptance of their disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations